PENERAPAN MODEL PEMBELAJARAN THE LEARNING CELL DALAM MENINGKATKAN HASIL BELAJAR DI SMAN 4 MAKASSAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The main problem in this study is how to apply the Learning Cell learning model in Islamic Religious Education (PAI) subject for class XI.3 at SMA Negeri 4 Makassar, and how the model can improve student learning outcomes. This study aims to determine the form of application of the Learning Cell learning model in improving student learning outcomes in the PAI subject. The type of research used is Classroom Action Research (CAR) which was carried out in two cycles. The subjects of this study were 32 class XI.3 students, consisting of 17 males and 15 females. The research instruments used included observation sheets to observe teacher and student activities during the learning process, as well as evaluation tests in the form of pre-tests and post-tests to measure learning outcomes before and after the action. The results showed that the application of the Learning Cell learning model was able to significantly improve student learning outcomes. In cycle I, the percentage of student learning completion reached 56.25% with an average score of 67.84%. Although there was an increase compared to the pre-cycle, the results had not yet reached the established success indicators. After improvements were made in cycle II, student learning outcomes improved significantly, with a completion rate of 87.5% and an average score of 86.56%. Therefore, it can be concluded that the implementation of The Learning Cell learning model is effective in improving student learning outcomes in Islamic Religious Education. Furthermore, this model is also able to increase student activeness, participation, and learning readiness in participating in the classroom learning process.